Effect of Pelleted Fermented Feed-in Egg Quality of Laying Hens - Aljebory, Hashim Hadi Dakhel; Naji, Saad A. H. (Diyala Agricultural Sciences Journal, 2021)
lactobacilli, Bacillus subtills, Bifidobacterium, Saccharomyces cerevisiae were applied to produce fermented feeds (FF), The FF was pelleted to investigated for its influences on egg quality for laying hens, the (FF) was ferment with 10 g / kg feed of the probiotic with a wetting ratio of half a liter/kg of feed for 48 hours where it was used at rates 0, 25%, 50 %, 75%, and 100% for the treatments T1, T2, T3, T4, and T5 respectively, and the duration of the study lasted for seven periods, each period was two weeks, as for the following study results: Significant superiority (P≤0.05) for all FF treatments during the second period and treatment T5 during the third and sixth periods, and for treatments T3, T4 and T5 during the fourth period in the shell weight. As for the shell thickness, a significant superiority (P≤0.01) was obtained for treatment T3 in the fourth period and for treatment T2 in the fifth, sixth, and seventh periods, and in the yolk height, there were a significant superiority (P≤0.01) for the treatment T4 during the first, second and seventh periods, and for the treatments T2 and T5 during the fourth and fifth periods, as for the yolk diameter, a significant superiority (P≤0.01)was obtained for the treatments T2, T3 and T4 in the fourth and fifth periods, and T2 during the seventh period, and in albumen height, a significant (P≤0.01) was increased for the treatments T3, T4, and T5 during the second period, and a significant superiority was obtained for treatment T5 in the fifth period and a significant superiority for the two treatments T1 and T2 in the seventh period.